The escape manual for introverts - Vaz, Katie (Andrews McMeel Publishing, 2019)
Trapped in an airplane seated next to a chatterbox? Are you hosting a dinner party with people who just won't leave? Katie Vaz has the key to your escape. The Escape Manual for Introverts guides readers through different scenarios with themed chapters ("Friends," "Relatives," "Strangers," etc.). Each chapter covers a range of situations, from an invitation to karaoke night to group lunchtime. And she offers a number of escapes for each scenario: bringing odoriferous foods to lunch for a while, having a pet (real or imagined) that "requires" frequent check-ins, and even investing in a jet pack. This book features Vaz's full-page illustrated spreads, hand-lettering, and spot illustrations. From the silly to the sincere, Vaz's clever, hilarious escape plans and bizarre excuses speak to the introvert in all of us.